PEMBERDAYAAN DISABILITAS DI MASA PANDEMI COVID-19 (DISABILITY EMPOWERMENT DURING THE COVID-19 PANDEMIC) - Salsabila Aurelia Pratiwi; Nurliana Cipta Apsari (Universitas Padjadjaran, 2022)
The COVID-19 pandemic which is endemic in various countries in the world including Indonesia has had an impact on various aspects of people's lives. The disabled community is one of the most affected by the COVID-19 pandemic, especially in the economic aspect because income has decreased so that they have difficulty in meeting their needs. One of the ways that can help persons with disabilities during the COVID-19 pandemic is through empowerment which can help increase their capacity to obtain their rights. This article describes the empowerment of persons with disabilities during the COVID-19 pandemic, especially in Indonesia. The method in this writing uses literature study obtained from various sources which is carried out by searching online for literature that is appropriate to the topic of writing and noting sources that are appropriate to the topic. The results of the study found that empowerment in the midst of the COVID-19 pandemic was generally carried out through entrepreneurial activities. Entrepreneurial activities are carried out by providing training to improve their skills in producing goods, marketing products and managing finances so that they continue to carry out productive activities to be able to generate income to meet their needs during the COVID-19 pandemic. Pandemi COVID-19 yang mewabah di berbagai negara di dunia termasuk Indonesia berakibat pada berbagai aspek kehidupan masyarakat. Masyarakat disabilitas adalah salah satu yang terdampak cukup besar dari adanya pandemi COVID-19 terutama pada aspek ekonomi dikarenakan pendapatan mengalami penurunan sehingga mereka kesulitan memenuhi kebutuhannya. Salah satu cara yang dapat membantu penyandang disabilitas di masa pandemi COVID-19 yaitu melalui pemberdayaan yang dapat membantu meningkatkan kapasitas mereka untuk memperoleh hak-haknya. Artikel ini mendeskripsikan pemberdayaan penyandang disabilitas di masa pandemi COVID-19 khususnya di Indonesia. Metode dalam penulisan ini menggunakan studi pustaka atau studi literatur yang diperoleh dari berbagai sumber yang dilakukan dengan cara mencari pustaka yang sesuai dengan topik penulisan secara online dan mencatat sumber yang sesuai dengan topik artikel. Berdasarkan hasil kajian, ditemukan bahwa pemberdayaan di tengah pandemi COVID-19 umumnya dilakukan dengan kegiatan kewirausahaan. Kegiatan kewirausahaan dilakukan dengan memberikan pelatihan untuk meningkatkan keterampilan mereka dalam memproduksi barang, pemasaran produk dan mengelola keuangan sehingga mereka tetap melakukan kegiatan yang produktif untuk dapat menghasilkan pendapatan guna memenuhi kebutuhan hidupnya dimasa pandemi COVID-19.